Preparation method of sodium-ion battery negative electrode by dry-method rapid homogenization
By using the combination of hard carbon, carboxymethylcellulose sodium, conductive carbon black, N-methylpyrrolidone, carbon nanotubes and specific bonding composite materials in the sodium ion battery negative electrode dry method rapid homogenization technology, the current solution is solved There are problems of low efficiency and poor quality in the technology, and the preparation of sodium ion battery negative electrode slurry with low resistivity and high Coulomb efficiency has been achieved.
Patent Information
- Application Number
- CN202411563928.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing sodium ion battery negative electrode drying fast homogenization technology has problems such as low stirring line speed, high equipment power, frequent equipment current alarm phenomena, uneven stirring, low solid content, long process flow time, and low efficiency, which affects working efficiency. and product quality.
A preparation method for rapid homogenization of sodium ion battery negative electrode dry method is adopted. By mixing hard carbon, sodium carboxymethylcellulose and conductive carbon black into powder, then adding N-methylpyrrolidone and carbon nanotubes for high-speed dispersion Finally, bonding composite materials containing maleic anhydride/styrene polymeric derivatives, humic acid graft copolymers and polynaphthaldehydesulfonic acid sodium salt were used to prepare sodium ions with low resistivity and high Coulombic efficiency. Battery negative electrode slurry.
The low resistivity and high Coulomb efficiency of the negative electrode slurry of sodium ion battery are achieved, which improves the stability and performance of the battery, reduces the resistivity to 3-6Ω, and improves the Coulomb efficiency to 85-99%.
Smart Images

Figure CN119480929A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery preparation, and in particular to a method for preparing a sodium ion battery negative electrode dry rapid homogenization. Background Art
[0002] Sodium-ion batteries are the representative of a new generation of green high-energy batteries. With their high voltage, high capacity, low consumption, no memory effect, environmental protection, small size, low internal resistance, low self-discharge and high cycle times, they have become one of the important directions for the development of high-tech. These characteristics make sodium-ion batteries show broad application prospects in passenger cars, electric buses, energy storage and other fields.
[0003] However, in the production process of batteries, although dry rapid homogenization technology is a relatively advanced process, there are still some problems in the existing technical design, such as low stirring line speed, high equipment power, frequent equipment current alarm phenomenon, uneven stirring, low solid content, long process time, low efficiency, etc. These problems not only affect work efficiency and product quality, but also put forward higher requirements on equipment capacity and reduce the service life of the equipment. Therefore, it is of practical significance and market prospects to develop a preparation method for dry rapid homogenization of sodium ion battery negative electrode. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a sodium ion battery negative electrode dry rapid homogenization to prepare a sodium ion battery negative electrode homogenate with low resistivity and high coulombic efficiency.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a sodium ion battery negative electrode dry rapid homogenization comprises: S1. Add hard carbon, sodium carboxymethyl cellulose and conductive carbon black into a stirring tank for powder mixing; S2, adding N-methylpyrrolidone for preliminary kneading to prepare a kneading slurry; S3, adding carbon nanotubes for high-speed dispersion to prepare a negative electrode high-speed dispersion slurry; S4. Add a bonding composite material, and adjust the viscosity and fineness of the slurry to obtain a negative electrode slurry for a sodium ion battery; the bonding composite material includes styrene-butadiene rubber and a bonding auxiliary agent; the bonding auxiliary agent includes at least a maleic anhydride / styrene polymer derivative and a humic acid graft copolymer, the maleic anhydride / styrene polymer derivative has a carboxyl group and a benzene ring, and the humic acid graft copolymer has a sulfonic acid group and a quaternary ammonium group.
[0006] The present invention first adds hard carbon, sodium carboxymethyl cellulose and conductive carbon black into a stirring tank for powder mixing, then sequentially adds N-methyl pyrrolidone and carbon nanotubes to prepare a negative electrode high-speed dispersed slurry, and finally uses a bonding composite material to evenly adhere the components of the negative electrode slurry together to prepare a sodium ion negative electrode slurry with low resistivity and high coulomb efficiency. The bonding composite material of the present invention includes styrene-butadiene rubber, maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, and has a large number of polar groups, which not only helps to maintain the stability of the negative electrode slurry during the battery charging and discharging process and prevent the active material from falling off; but also can improve the electrochemical performance of the negative electrode slurry, including reducing the resistivity and improving the coulomb efficiency.
[0007] Preferably, in the preparation of the maleic anhydride / styrene polymer derivative, maleic anhydride and styrene are used as raw materials, divinylbenzene is added to react, and the maleic anhydride / styrene polymer derivative is obtained.
[0008] Preferably, the preparation of maleic anhydride / styrene polymer derivatives is specifically as follows: Weigh maleic anhydride and sucrose, add toluene and stir evenly, add styrene and divinylbenzene, pass nitrogen for 20-40 minutes, add azobisisobutyronitrile, carry out polymerization reaction at 50-80°C for 2-10 hours, wash with toluene 2-5 times after high-speed centrifugation, freeze-dry in vacuum, add sodium hydroxide solution, stir at 50-70°C for 1-3 hours, and ultrasonically treat to obtain maleic anhydride / styrene polymerization derivatives.
[0009] More preferably, the weight ratio of maleic anhydride to sucrose is 1:10-30.
[0010] More preferably, the usage ratio of sucrose to toluene is 1 g:10-40 mL.
[0011] More preferably, the weight ratio of styrene to maleic anhydride is 1:1-2.
[0012] More preferably, the weight ratio of divinylbenzene to styrene is 1:1-3.
[0013] More preferably, the weight ratio of azobisisobutyronitrile to maleic anhydride is 1:0.1-0.5.
[0014] More preferably, the volume ratio of the sodium hydroxide solution to toluene is 1:0.2-1, and the mass concentration of the sodium hydroxide solution is 1-5%.
[0015] Preferably, in the preparation of the humic acid graft copolymer, humic acid, sodium allyl sulfonate and dimethyldiallylammonium chloride are used as raw materials, potassium persulfate is added to carry out free radical polymerization reaction, and the humic acid graft polymer is obtained.
[0016] Preferably, the preparation of the humic acid graft copolymer comprises: Humic acid was dissolved in water, 10% sodium hydroxide solution was added to adjust the pH to 9, sodium allyl sulfonate and dimethyldiallylammonium chloride were added, potassium persulfate was added, the temperature was raised to 80°C under nitrogen protection, the reaction was continued for 2.5 hours, the mixture was cooled to room temperature, the mixture was filtered under reduced pressure, the pH was adjusted to neutral with dilute hydrochloric acid, and a humic acid grafted copolymer was obtained.
[0017] More preferably, the usage ratio of humic acid to water is 1 g: 2-10 mL.
[0018] More preferably, the weight ratio of sodium allyl sulfonate to humic acid is 1:1-5.
[0019] More preferably, the weight ratio of sodium allyl sulfonate to dimethyldiallylammonium chloride is 1:0.1-0.5.
[0020] More preferably, the weight ratio of potassium persulfate to dimethyldiallylammonium chloride is 1:0.5-1.5.
[0021] Preferably, the weight ratio of sodium carboxymethyl cellulose to hard carbon is 1:50-100.
[0022] Preferably, the weight ratio of the conductive carbon black to the sodium carboxymethyl cellulose is 1:1-3.
[0023] Preferably, the weight ratio of N-methylpyrrolidone to sodium carboxymethylcellulose is 1:1-2.
[0024] Preferably, the weight ratio of carbon nanotubes to hard carbon is 1:7-8.
[0025] Preferably, the weight ratio of the bonding composite material to the hard carbon is 1:10-15.
[0026] Preferably, a method for preparing a sodium ion battery negative electrode dry rapid homogenization comprises: S1. Weigh hard carbon, sodium carboxymethyl cellulose and conductive carbon black, stir at 5-10 rpm and 0-5 rpm for 1-5 min, and then stir at 20-40 rpm and 400-600 rpm for 20-40 min to mix the powders; S2. Add water to the mixed powder for the first time, then add N-methylpyrrolidone, stir at a revolution of 5-20 rpm and a rotation of 0-5 rpm for 5-20 min for preliminary kneading, and then stir at a revolution of 20-40 rpm and a rotation of 0-5 rpm for 60-120 min to prepare a kneading slurry; S3, adding carbon nanotubes to the kneaded slurry, stirring at a revolution of 20-40 rpm and a rotation of 2000-2500 rpm for 30-90 min for high-speed dispersion, adding water for a second time, and stirring at a revolution of 20-40 rpm and a rotation of 2000-2500 rpm for 20-40 min for high-speed dispersion, to prepare a negative electrode high-speed dispersion slurry; S4, stirring at an orbital speed of 5-10 rpm and an autorotation speed of 0-5 rpm for 5-20 min, cooling to 25-40° C., adding a bonding composite material, stirring at an orbital speed of 10-30 rpm and an autorotation speed of 500-1000 rpm for 20-60 min, adding water for the third time and stirring at an orbital speed of 10-30 rpm and an autorotation speed of 500-1000 rpm for 20-40 min until the viscosity of the slurry reaches 800-3000 cp and the fineness reaches 10-30 μm, stirring at an orbital speed of 5-20 rpm and an autorotation speed of 0-5 rpm for 20-40 min under vacuum conditions for degassing treatment to obtain a negative electrode slurry for a sodium ion battery.
[0027] More preferably, the weight ratio of sodium carboxymethyl cellulose to hard carbon is 1:50-100.
[0028] More preferably, the weight ratio of the conductive carbon black to the sodium carboxymethyl cellulose is 1:1-3.
[0029] More preferably, the weight ratio of the first added water to the hard carbon is 1:1.5-2.5.
[0030] More preferably, the weight ratio of N-methylpyrrolidone to sodium carboxymethylcellulose is 1:1-2.
[0031] More preferably, the weight ratio of carbon nanotubes to hard carbon is 1:7-8.
[0032] More preferably, the weight ratio of the second added water to the hard carbon is 1:20-40.
[0033] More preferably, the weight ratio of the bonding composite material to the hard carbon is 1:10-15.
[0034] More preferably, the bonding composite comprises styrene butadiene rubber.
[0035] Preferably, in the preparation of a sodium ion battery negative electrode dry rapid homogenization, maleic anhydride / styrene polymer derivatives and humic acid graft copolymers are also used as bonding auxiliary agents to form a bonding composite material, and then the bonding composite material is used to prepare sodium ion negative electrode slurry.
[0036] More preferably, the bonding composite material comprises styrene-butadiene rubber, maleic anhydride / styrene polymer derivatives and humic acid graft copolymer.
[0037] More preferably, the weight ratio of styrene-butadiene rubber to maleic anhydride / styrene polymer derivative is 1:0.05-0.1.
[0038] More preferably, the weight ratio of styrene-butadiene rubber to humic acid graft copolymer is 1:0.01-0.05.
[0039] Preferably, in the preparation of a sodium ion battery negative electrode dry rapid homogenization, polynaphthaldehyde sulfonic acid sodium salt is also used as a bonding auxiliary agent to form a bonding composite material, and the bonding composite material is then used to prepare a sodium ion negative electrode slurry. Polynaphthaldehyde sulfonic acid sodium salt is a high molecular polymer that can further help adhere and disperse the active material in the slurry, improve the stability of the battery, thereby further reducing the resistivity of the battery negative electrode slurry and improving the coulombic efficiency of the battery.
[0040] More preferably, the bonding composite material comprises styrene-butadiene rubber, maleic anhydride / styrene polymer derivative, humic acid graft copolymer and polynaphthalene formaldehyde sulfonic acid sodium salt.
[0041] More preferably, the weight ratio of styrene-butadiene rubber to maleic anhydride / styrene polymer derivative is 1:0.05-0.1.
[0042] More preferably, the weight ratio of styrene-butadiene rubber to humic acid graft copolymer is 1:0.01-0.05.
[0043] More preferably, the weight ratio of styrene-butadiene rubber to sodium polynaphthalene sulfonate is 1:0.002-0.01.
[0044] The present invention uses maleic anhydride / styrene polymer derivatives, humic acid graft copolymers and polynaphthaldehyde sulfonic acid sodium salt to form a bonding composite material, and then uses the bonding composite material to prepare the negative electrode slurry of the battery, so it has the following beneficial effects: maleic anhydride / styrene polymer derivatives, humic acid graft copolymers and polynaphthaldehyde sulfonic acid sodium salt are all high molecular polymers with a large number of polar groups, which are helpful to bond the active substances in the negative electrode slurry of the battery together, help to reduce the resistivity of the battery, and improve the coulomb efficiency of the battery. The resistivity of the negative electrode slurry prepared by the present invention is 3-6Ω, and the coulomb efficiency is 85-99%. Therefore, the present invention provides a method for preparing a dry method for rapid homogenization of a negative electrode of a sodium ion battery with low resistivity and high coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the infrared spectrum of the maleic anhydride / styrene polymer derivative obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0047] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0048] Embodiment 1: S1. Preparation of negative electrode slurry, including: S11. Weigh hard carbon, sodium carboxymethyl cellulose and conductive carbon black, stir at an orbital speed of 5 rpm and an autorotation speed of 0 rpm for 3 min, and then stir at an orbital speed of 30 rpm and an autorotation speed of 500 rpm for 30 min to mix the powders.
[0049] S12. Add water to the mixed powder for the first time, then add N-methylpyrrolidone, stir at an orbital speed of 10 rpm and an autorotation speed of 0 rpm for 10 min for preliminary kneading, then stir at an orbital speed of 30 rpm and an autorotation speed of 0 rpm for 90 min for kneading to prepare a kneaded slurry.
[0050] S13, adding carbon nanotubes to the kneaded slurry, stirring at 30 rpm and 2200 rpm for 60 min for high-speed dispersion, adding water for the second time, stirring at 30 rpm and 2200 rpm for 30 min for high-speed dispersion, to prepare a negative electrode high-speed dispersion slurry.
[0051] S14, stirring at an orbital speed of 5 rpm and an autorotation speed of 0 rpm for 10 min, cooling to 30°C, adding a bonding composite material, stirring at an orbital speed of 20 rpm and an autorotation speed of 800 rpm for 40 min, adding water for the third time and stirring at an orbital speed of 20 rpm and an autorotation speed of 800 rpm for 30 min until the viscosity of the slurry reaches 1500 cp and the fineness reaches 30 μm, stirring at an orbital speed of 10 rpm and an autorotation speed of 0 rpm for 30 min under vacuum conditions for degassing treatment to obtain a sodium ion negative electrode slurry.
[0052] In this embodiment, the weight ratio of sodium carboxymethyl cellulose and hard carbon is 1:63, the weight ratio of conductive carbon black and sodium carboxymethyl cellulose is 1:2.12, the weight ratio of the first water addition and hard carbon is 1:1.76, the weight ratio of N-methylpyrrolidone and sodium carboxymethyl cellulose is 1:1.58, the weight ratio of carbon nanotubes and hard carbon is 1:7.64, and the weight ratio of the second water addition and hard carbon is 1:31.25; the bonding composite material includes styrene-butadiene rubber, and the weight ratio of the bonding composite material and hard carbon is 1:12.5.
[0053] Embodiment 2: S1. Preparation of maleic anhydride / styrene polymer derivatives, comprising: Weigh maleic anhydride and sucrose, add toluene and stir evenly, add styrene and divinylbenzene, pass nitrogen for 30 minutes, add azobisisobutyronitrile, polymerize at 65°C for 4 hours, wash with toluene 3 times after high-speed centrifugation, freeze-dry in vacuum, add sodium hydroxide solution, stir at 60°C for 2 hours, and ultrasonically treat to obtain maleic anhydride / styrene polymer derivatives. The weight ratio of maleic anhydride to sucrose is 1:20, the dosage ratio of sucrose to toluene is 1g:25mL, the weight ratio of styrene to maleic anhydride is 1:1.67, the weight ratio of divinylbenzene to styrene is 1:2, the weight ratio of azobisisobutyronitrile to maleic anhydride is 1:0.25, the volume ratio of sodium hydroxide solution to toluene is 1:0.5, and the mass concentration of sodium hydroxide solution is 3%.
[0054] S2. Preparation of humic acid graft copolymer, comprising: Humic acid was dissolved in water, and a 10% sodium hydroxide solution was added to adjust the pH to 9, sodium allyl sulfonate and dimethyl diallyl ammonium chloride were added, and potassium persulfate was added. The temperature was raised to 80°C under nitrogen protection for 2.5 hours, cooled to room temperature, filtered under reduced pressure, and the pH was adjusted to neutral with dilute hydrochloric acid to obtain a humic acid graft copolymer. The dosage ratio of humic acid to water was 1g:5mL, the weight ratio of sodium allyl sulfonate to humic acid was 1:2, the weight ratio of sodium allyl sulfonate to dimethyl diallyl ammonium chloride was 1:0.3, and the weight ratio of potassium persulfate to dimethyl diallyl ammonium chloride was 1:0.77.
[0055] S3, preparation of negative electrode slurry, except that the components of the bonding composite material are changed, other conditions are the same as those in Example 1. In this example, the bonding composite material includes styrene-butadiene rubber, maleic anhydride / styrene polymer derivative and humic acid graft copolymer, the weight ratio of styrene-butadiene rubber to maleic anhydride / styrene polymer derivative is 1:0.06, and the weight ratio of styrene-butadiene rubber to humic acid graft copolymer is 1:0.03.
[0056] Embodiment 3: Except that the weight ratio of styrene-butadiene rubber and maleic anhydride / styrene polymer derivative was changed to 1:0.03 in the preparation of the negative electrode slurry, other conditions were the same as those in Example 2.
[0057] Embodiment 4: Except that the weight ratio of styrene-butadiene rubber and humic acid graft copolymer was changed to 1:0.015 in the preparation of negative electrode slurry, other conditions were the same as those in Example 2.
[0058] Embodiment 5: S1. Preparation of maleic anhydride / styrene polymer derivatives, same as in Example 2.
[0059] S2. Preparation of humic acid graft copolymer is the same as in Example 2.
[0060] S3, preparation of negative electrode slurry, except that the components of the bonding composite material are changed, other conditions are the same as in Example 1. In this embodiment, the bonding composite material includes styrene-butadiene rubber, maleic anhydride / styrene polymer derivative, humic acid graft copolymer and polynaphthalene formaldehyde sulfonate sodium salt, the weight ratio of styrene-butadiene rubber to maleic anhydride / styrene polymer derivative is 1:0.06, the weight ratio of styrene-butadiene rubber to humic acid graft copolymer is 1:0.03, and the weight ratio of styrene-butadiene rubber to polynaphthalene formaldehyde sulfonate sodium salt is 1:0.01.
[0061] Embodiment 6: Except that the weight ratio of styrene-butadiene rubber and sodium polynaphthalene sulfonate was changed to 1:0.005 in the preparation of the negative electrode slurry, other conditions were the same as those in Example 5.
[0062] Comparative Example 1: S1. Preparation of maleic anhydride / styrene polymer derivatives, same as in Example 2.
[0063] S2. Preparation of negative electrode slurry, except for the change of the composition of the bonding composite material, other conditions are the same as those in Example 1. In this example, the bonding composite material includes styrene-butadiene rubber and maleic anhydride / styrene polymer derivative, and the weight ratio of styrene-butadiene rubber to maleic anhydride / styrene polymer derivative is 1:0.06.
[0064] Comparative Example 2: S1. Preparation of humic acid graft copolymer, same as Example 2.
[0065] S2. Preparation of negative electrode slurry, except for the change of the components of the bonding composite material, other conditions are the same as those in Example 1. In this example, the bonding composite material includes styrene-butadiene rubber and humic acid graft copolymer, and the weight ratio of styrene-butadiene rubber to humic acid graft copolymer is 1:0.03.
[0066] Comparative Example 3: S1. Preparation of negative electrode slurry, except for the change of the components of the bonding composite material, other conditions are the same as those in Example 1. In this example, the bonding composite material includes styrene-butadiene rubber and polynaphthalene formaldehyde sulfonate sodium salt, and the weight ratio of styrene-butadiene rubber to polynaphthalene formaldehyde sulfonate sodium salt is 1:0.01.
[0067] Experimental example: 1. Material Characterization The infrared spectrum of the sample was measured by Fourier transform infrared spectrometer using KBr pellet method at wave number 4000-400 cm -1Measurement within the range, resolution 0.06cm -1 , scanned 32 times.
[0068] Figure 1 This is the infrared spectrum of the maleic anhydride / styrene polymer derivative obtained in Example 2 of the present invention, 2970 cm -1 and 2830cm -1 The absorption peak of CH appears near 1710 cm -1 The absorption peak of carboxyl group appears near 1630cm -1 and 1490cm -1 The absorption peak of benzene ring C=C appears nearby, 1225cm -1 The absorption peak of COC appears nearby.
[0069] 2. Determination of resistivity The negative electrode slurries obtained in Examples 1-6 and Comparative Examples 1-4 were uniformly coated on 16 μm thick aluminum foil, with a coating thickness of 120 μm. They were vacuum dried at 80° C. for 12 h to produce negative electrode sheets with a diameter of 12 mm. The resistivity of the negative electrode sheets was tested with a resistance meter at a test pressure of 5 MPa. The test results are shown in Table 1.
[0070] Table 1 Resistivity measurement results
[0071] As can be seen from Table 1, the resistivity of Example 2 is lower than that of Example 1 because, in the components of the bonding composite material, Example 1 uses styrene-butadiene rubber, while Example 2, on the basis of using styrene-butadiene rubber, also adds maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, which shows that the method of Example 2 can effectively reduce the resistivity. The resistivity of Example 2 is lower than that of Comparative Examples 1-2 because, in the components of the bonding composite material, Example 2 adds maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, while Comparative Example 1 only adds maleic anhydride / styrene polymer derivatives, and Comparative Example 2 only adds humic acid graft copolymers; the resistivity of Example 2 is lower than that of Examples 3-4 because, in the components of the bonding composite material, the amounts of maleic anhydride / styrene polymer derivatives and humic acid graft copolymers are different. This shows that in the components of the bonding composite material, the coordinated use of maleic anhydride / styrene polymer derivatives and humic acid graft copolymers makes the effect of reducing resistivity better. The resistivity of Example 5 is lower than that of Example 2 because in the components of the bonding composite material, Example 5 further adds sodium polynaphthaldehyde sulfonate; the resistivity of Example 5 is lower than that of Comparative Example 3 because in the components of the bonding composite material, sodium polynaphthaldehyde sulfonate is added separately in Comparative Example 3; the resistivity of Example 5 is lower than that of Example 6 because in the components of the bonding composite material, the amount of sodium polynaphthaldehyde sulfonate used is different. This shows that further adding sodium polynaphthaldehyde sulfonate to the components of the bonding composite material can further reduce the resistivity.
[0072] 3. Determination of Coulombic efficiency The negative electrode slurries obtained in Examples 1-6 and Comparative Examples 1-4 were uniformly coated on 16 μm thick aluminum foil, with a coating thickness of 120 μm, and vacuum dried at 80°C for 12 hours to form a negative electrode sheet with a diameter of 12 mm, and then assembled into a CR2025 button cell using glass fiber as a separator. A constant current charge and discharge test was performed using a battery charge and discharge tester, with a voltage of 0.01-2.50 V. The battery was first discharged to 0.01 V, left for 5 minutes, and then charged to 2.50 V. The coulomb efficiency was calculated, coulomb efficiency (%) = discharge specific capacity / charge specific capacity × 100%, and the measurement results are shown in Table 2.
[0073] Table 2 Coulombic efficiency measurement results
[0074] As can be seen from Table 2, the coulombic efficiency of Example 2 is higher than that of Example 1 because, in the components of the bonding composite material, Example 1 uses styrene-butadiene rubber, while Example 2, on the basis of using styrene-butadiene rubber, also adds maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, which shows that the method of Example 2 can effectively improve the coulombic efficiency. The coulombic efficiency of Example 2 is higher than that of Comparative Examples 1-2 because, in the components of the bonding composite material, Example 2 adds maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, while Comparative Example 1 only adds maleic anhydride / styrene polymer derivatives, and Comparative Example 2 only adds humic acid graft copolymers; the coulombic efficiency of Example 2 is higher than that of Examples 3-4 because, in the components of the bonding composite material, the amounts of maleic anhydride / styrene polymer derivatives and humic acid graft copolymers are different. This shows that in the components of the bonding composite material, the coordinated use of maleic anhydride / styrene polymer derivatives and humic acid graft copolymers makes the effect of improving the coulombic efficiency better. The coulombic efficiency of Example 5 is higher than that of Example 2 because, in the components of the bonding composite material, Example 5 further adds polynaphthaldehyde sodium sulfonate; the coulombic efficiency of Example 5 is higher than that of Comparative Example 3 because, in the components of the bonding composite material, Comparative Example 3 alone adds polynaphthaldehyde sodium sulfonate; the coulombic efficiency of Example 5 is higher than that of Example 6 because, in the components of the bonding composite material, the usage amount of polynaphthaldehyde sodium sulfonate is different. This shows that further adding polynaphthaldehyde sodium sulfonate to the components of the bonding composite material can further improve the coulombic efficiency.
[0075] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.
[0076] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium ion battery negative electrode dry rapid homogenization, comprising: S1. Add hard carbon, sodium carboxymethyl cellulose and conductive carbon black into a stirring tank for powder mixing; S2, adding N-methylpyrrolidone for preliminary kneading to prepare a kneading slurry; S3, adding carbon nanotubes for high-speed dispersion to prepare a negative electrode high-speed dispersion slurry; S4, adding the bonding composite material, and adjusting the viscosity and fineness of the slurry to obtain a negative electrode slurry for a sodium ion battery; The bonding composite material includes styrene-butadiene rubber and a bonding auxiliary agent; the bonding auxiliary agent at least includes maleic anhydride / styrene polymer derivatives and humic acid graft copolymers, the maleic anhydride / styrene polymer derivatives have carboxyl groups and benzene rings, and the humic acid graft copolymers have sulfonic acid groups and quaternary ammonium groups.
2. A bonding composite material according to claim 1, characterized in that: In the preparation of the maleic anhydride / styrene polymer derivative, maleic anhydride and styrene are used as raw materials, divinylbenzene is added to react, and the maleic anhydride / styrene polymer derivative is obtained.
3. A bonding composite material according to claim 1, characterized in that: In the preparation of the humic acid graft copolymer, humic acid, sodium allyl sulfonate and dimethyl diallyl ammonium chloride are used as raw materials, potassium persulfate is added to carry out free radical polymerization reaction, and the humic acid graft polymer is obtained.
4. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The weight ratio of the sodium carboxymethyl cellulose to the hard carbon is 1:50-100.
5. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The weight ratio of the conductive carbon black to sodium carboxymethyl cellulose is 1:1-3.
6. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The weight ratio of the N-methylpyrrolidone to sodium carboxymethylcellulose is 1:1-2.
7. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The weight ratio of the carbon nanotubes to the hard carbon is 1:7-8.
8. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The weight ratio of the bonding composite material to the hard carbon is 1:10-15.
9. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The viscosity of the slurry is 800-3000cp.
10. The method for preparing a sodium ion battery negative electrode dry rapid homogenization according to claim 1, characterized in that: The fineness of the slurry is 10-30 μm.